2006
DOI: 10.1017/s1368980007668530
|View full text |Cite
|
Sign up to set email alerts
|

Importance of functional foods in the Mediterranean diet

Abstract: Objective: Analyse the importance of components of Mediterranean diet in functional feeding. Design: We have based the study in a bibliographic review. Results: Many of the characteristic components of the traditional Mediterranean diet (MD) are known to have positive effects on health, capacity and well-being, and can be used to design functional foods. Vegetables, fruits and nuts are all rich in phenols, flavonoids, isoflavonoids, phytosterols and phytic acid-essential bioactive compounds providing health be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 25 publications
3
92
0
9
Order By: Relevance
“…Majority 269(87.9%) of the respondents started their menstruation between 10-13 years, this is in agreement with Ortega, [19] when they concluded that the age of menarche was between <11 and >12 years.…”
Section: Discussionsupporting
confidence: 85%
“…Majority 269(87.9%) of the respondents started their menstruation between 10-13 years, this is in agreement with Ortega, [19] when they concluded that the age of menarche was between <11 and >12 years.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to their healthy diet, Mediterranean people had regular physical activity, usually required for field or kitchen work and outdoor leisure activities (2,5) . The great richness and diversity of plants in the Mediterranean region provide numerous functional foods (FF) that improve state of health and/or provide a reduction in the risk of disease (6) , like olive oil, yoghurt, garlic, tomato, wine, condiments, herbs, spices and nuts (7) . In addition to FF, the MD is rich in functional dietary components like phenols, flavonoids, isoflavonoids, phytosterols, phytic acid and n-3 fatty acids (7) .…”
mentioning
confidence: 99%
“…Hortalizas, frutas y frutos secos son ricos en fenoles, flavonoides, isoflavonoides, fitosteroles, ácidos grasos insaturados, vitaminas C y E, todos ellos compuestos bioactivos beneficiosos para la salud (78,79).…”
Section: Prevención De Daño Endotelial Por Frutas Y Hortalizas Nutrigunclassified